Efficiency analysis of Islamic banks in the Middle East and North Africa region: A bootstrap DEA approach - Raéf Bahrini (International Journal of Financial Studies, 2017)
This paper measures and analyzes the technical efficiency of Islamic banks in the Middle East and North Africa (MENA) region during the period 2007-2012. To do this, the bootstrap Data Envelopment Analysis (DEA) approach was employed in order to provide a robust estimation of the overall technical efficiency and its components: pure technical efficiency and scale efficiency in the case of MENA Islamic banks. The main results show that over the period of study, pure technical inefficiency was the main source of overall technical inefficiency instead of scale inefficiency. This finding was confirmed for all MENA Islamic banks as well as for the two subsamples: Gulf Cooperation Council (GCC) and non-GCC Islamic banks. Furthermore, our results show that GCC Islamic banks had stable efficiency scores during the global financial crisis (2007-2008) and in the early post-crisis period (2009-2010). However, a decline in overall technical efficiency of all panels of MENA Islamic banks was recorded in the last two years of the study period (2011-2012). Thus, we recommend that MENA Islamic bank managers focus more on improving their management practices rather than increasing their sizes. We also recommend that financial authorities in MENA countries implement several regulatory and financial measures in order to ensure the development of MENA Islamic banking.
Keywords: C15; C61; G21; 330; technical efficiency; Islamic banks; MENA region; GCC; non-GCC; bootstrap DEA